Preface - Alfredo Ulloa-Aguirre; David Kershenobich-Stalnikowitz (Permanyer, 2021)
This year, the Instituto Nacional de Ciencias Médicas y Nutrición Salvador Zubirán (INCMNSZ) (National Institute of Medical Sciences and Nutrition) celebrates 75 years of existence.